Okołotarczowa degeneracja naczyniówki i siatkówki - Brydak-Godowska, Joanna; Dróbecka-Brydak, Ewa; Świtka-Bachnik, Elżbieta; Ciszewska, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Helicoidal peripapillary chorioretinal degeneration (HCPD) is characterized by bilateral wing- shaped atrophic areas in retina, radiating from the optic disc. Two cases (women: 23 and 58 years old) of this rare degeneration are presented. No changes of eye fundus and erg, eog, visual field evaluations had been noticed during 2 years follow-up.